Language society activities 2017 - Kadri, Affiana (UiTM Sarawak, 2018)
On 24 and 25 November 2017, a Public Speaking “Speak-lt-Right” competition was successfully organised by UiTM Sarawak Language Society. This academic activity was held to promote students’ interest and awareness on the importance of public speaking. The competition was divided into two categories namely Diploma and Degree levels. During the preliminary round, the participants were given the task of delivering an Impromptu Speech while for the Final Round, the qualified participants were given the task of delivering a Prepared Speech. The advisor, Miss Siti Huzaimah binti Hj. Sahari, the Language Coordinator of UiTM Sarawak, was very supportive of the event. The organising committee was headed by Associate Professor Dr. Caesar Dealwis and Mr. Abang Fhaeizdhyall bin Abang Madaud who were assisted by UiTM Sarawak language lecturers and Language Society student committee members. The two-day event brought many wonderful memories for students and lecturers. The committee looks forward to extending this competition to involve the whole campus in the future.